Validitas, Reliabilatas dan Dampak Pembelajaran terhadap Tes Objective Structured Clinical Examintaion (OSCE) - Ashaeryanto Ashaeryanto (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2016)
Objective Structured Clinical Examination (OSCE) was developed for the first time by Harden at1975 which was used for evaluating clinical skill ability of OSCE Implementation that could give learning positive and negative impact. Objective: To explain validity, reliability of OSCE and investigate OSCE Test Implementation (Objective Structured Clinical Examintaion) impact to learning, especially in study behavior aspect.  Discussion: Van  Der  Vleuten  explains that  OSCE  is  a  good  and  useful  method  in  clinical skill evaluation which is based on 5 criterias namely OSCE test have reliability, validity, educational impact, cost efficiency, acceptability. Reliability can be seen in examiner consistency, case variation, and implementation in prosperous time. OSCE have high content, face, concurernt, and construct validity. OSCE can give positive and negative learning impact.Keywords: OSCE, educational impact, performance assessments,validity